Antifeedant activity and effects of terpenoids on detoxication enzymes of the beet armyworm, Spodoptera exigua (Hübner) - Caballero, C.; López-Olguín, J.; Ruiz, M.; Ortego, F.; Castañera, P. (Spanish Journal of Agricultural Research, 2008)
It has been determined the antifeedant activity of a mixture of limonoids 1,7-di-O-acetylhavanensin and 3,7-di-Oacetylhavanensin (F18), isolated from seeds of Trichilia havanensis Jacq. (Meliaceae), and the neo-clerodane diterpene scutecyprol A, isolated from Scutellaria valdiviana (Clos) Epling (Labiatae), on fifth instar larvae of the beet armyworm, Spodoptera exigua (Hübner) (Lepidoptera: Noctuidae). Choice and no-choice feeding assays, nutritional tests, and post-treatment studies indicated that scutecyprol A acts as an insect feeding deterrent against S. exigua, whereas the antifeedant activity of F18 is likely associated with a toxic mode of action. In addition, it was tested the hypothesis that S. exigua larvae will try to metabolize the compounds that are toxic by the induction of their detoxication systems, whereas no such induction happens for those compounds that are deterrents. The mixture of limonoids F18 significantly increased glutathione S-transferases during the treatment and post-treatment periods, whereas esterases were inhibited during the treatment period. On the contrary, scutecyprol A did not have any significant effect on any of the enzymatic processes. Hence, the metabolic response of S. exigua larvae to the ingestion of the secondary metabolites tested depends on their mode of action.